(untitled) (ANGON: Journal of Animal Science and Technology, 2020)
Background. Research entitled "Concentrated Substitution with Snail Flour In Laying Commercial Chicken Feed On Weight And Thick Eggshell". The purpose of this study was to examine the effect of substitution of concentrate with conch flour on the weight and thickness of laying commercial chicken shells. Materials and methods. The research material consisted of 80 commercial laying hens. The feed ingredients used are concentrates, conch flour, corn and bran. The study was conducted experimentally using a Completely Randomized Design (CRD), with 4 treatments and 5 replications, each repetition consisted of 4 laying hens. The treatments consisted of R0: Basal feed without conch flour substitution, R1: Basal feed with 5% conch flour substitution, R2: Basal feed with 10% conch flour substitution, R3: Basal feed with 15% conch flour substitution. Results. The results of the average eggshell weight of the treatments R0, R1, R2, R3 are 7.14; 6.45; 6.87; 6.90 and eggshell thickness is 0.27; 0.26; 0.26; 0.27. Based on the results of the study that the substitution of conch flour has no significant effect (P> 0.05) on the weight and thickness of egg laying hens. Conclusion. The substitution of concentrate with conch flour in laying commercial chicken feed up to 15% resulting in relatively equal quality weight and thickness of egg laying hens.